Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/su14105856
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Clay Mineral Amendments Characteristics on Heavy Metals Uptake in Vetiver Grass (Chrysopogon zizanioides L. Roberty) and Indian Mustard (Brassica juncea L. Czern)

Abstract: Phytoremediation is limited when heavy metals reduce soil quality and, subsequently, inhibit plant growth. In this study, we evaluated the use of attapulgite and bentonite as amendments in soil contaminated with multiple metals, to improve the phytoremediation capacity of Vetiver grass and Indian mustard. A 21-day greenhouse study was undertaken, to investigate plant tolerance in heavy-metal-contaminated soil, as well as heavy-metal absorption in plant roots and shoots. The results showed a generally higher ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…In this study, we aimed to examine the efficiency of an optimised hybrid application of vetiver grass and clay minerals for remediation of soil and water contaminated with heavy metals (Al and Mn in water; and Co, Cr, Cu, Ni and Zn in soil) in a mesocosm setting as informed by success in previous greenhouse studies. 16,17 There is little documentation of mesocosm studies concerning assisted phytoremediation of soil and water [27][28][29] ; therefore, this study contributes to the repository of available studies of phytoremediation in mesocosms, further encouraging its application.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…In this study, we aimed to examine the efficiency of an optimised hybrid application of vetiver grass and clay minerals for remediation of soil and water contaminated with heavy metals (Al and Mn in water; and Co, Cr, Cu, Ni and Zn in soil) in a mesocosm setting as informed by success in previous greenhouse studies. 16,17 There is little documentation of mesocosm studies concerning assisted phytoremediation of soil and water [27][28][29] ; therefore, this study contributes to the repository of available studies of phytoremediation in mesocosms, further encouraging its application.…”
Section: Introductionmentioning
confidence: 89%
“…Major examples of clay minerals include attapulgite, bentonite, montmorillonite, zeolite and kaolinite. 13 Previous studies by Otunola et al 16,17 showed that attapulgite administered at 2.5% (w/w) was most effective to improve the phytoremediation capacity of vetiver grass in metals polluted soil, while bentonite administered at 2.5% (w/v) was best for water remediation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, it was developed in 1985 by the World Bank to protect India's soil and water [21]. The system contributes to the procedures of agricultural land management [33], environmental protection [63], soil and water conservation [64], infrastructure balancing [65], contamination management [23], as well as water and wastewater treatment [66][67][68]. The origin of the Chryspogon zizanioides species is in South India [69].…”
Section: Vetiver Systemmentioning
confidence: 99%
“…as stabilizing materials of repair technologies can absorb interlayer toxic cations and can fix ions in the crystal structure. The clay minerals as passivate contaminants can change the existing forms of pollutants in the soil and can reduce their mobility and bioavailability in the environment, which can deactivate pollutants [13,14]. The research conducted by Liu et al revealed that the application of phosphate rock and zeolite separately to soil led to a significant reduction in the bioavailability of Cd in the soil and changed the soluble, exchangeable, and specifically sorbed fractions to oxide-bound and organic-bound fractions, effectively remediating Cd-contaminated soil [15].…”
Section: Introductionmentioning
confidence: 99%